Anaerobic treatment of glutamate-rich wastewater in a continuous UASB reactor: Effect of hydraulic retention time and methanogenic degradation pathway. (April 2020) - Chen, Hong; Wei, Yanxiao; Xie, Chenglei; Wang, Hong; Chang, Sheng; Xiong, Ying; Du, Chunyan; Xiao, Benyi; Yu, Guanlong
Abstract: To investigate the anaerobic treatment efficiency and degradation pathways of glutamate-rich wastewater under various hydraulic retention times (HRTs), a lab-scale upflow anaerobic sludge blanket (UASB) reactor was operated continuously for 180 days. Results showed that high chemical oxygen demand (COD) removal efficiencies of 95.5%–96.5% were achieved at HRTs of 4.5 h–6 h with a maximum methane yield of 0.31 L-CH4 /g-COD. When the HRT was shortened to less than 3 h, the removal performance of the reactor declined. There also was an excessive accumulation of volatile fatty acids, which implies that an appropriately small HRT is applicable to the UASB reactor treating glutamate-rich wastewater. Methanogenic degradation of glutamate in the UASB reactor depended on the HRT applied, and the typical methane-producing capability of the sludge at an HRT of 3 h, in descending order, was acetate > glutamate > butyrate > H2 /CO2  > valerate > propionate. Clostridium and Methanosaeta were predominant in the glutamate-degrading sludge. At least three degradation pathways most likely existed in the UASB reactor, and the pathway via 3-methlaspartate by Clostridium pascui was expected to be dominant. Graphical abstract: Image 1 Highlights: Methanogenic degradation of glutamate in UASB reactor depended on HRT applied. High MSG removal and energy recovery obtained at HRTs of 4.5–6 h. Clostridium and Methanosaeta were predominant in glutamate-degrading granules. HRT had substantial impact on SMA and microbial community of granules. The pathway via 3-methlaspartate was dominant for methanogenic degradation.